2021
DOI: 10.3390/app11062665
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Analysis of Adhesive Types and Bonding Mistakes on Bonded-in-Rod (BiR) Connections for Timber Structures

Abstract: Bonded-in rods (BiR) represent a structural connection type that is largely used for new timber structures and rehabilitation (repair or reinforcement) of existing structural members. The technology is based on steel / Fiber Reinforced Polymer (FRP) / Glass Fiber Reinforced Polymer (GFRP) rods bonded into predrilled holes in timber elements. The mechanical advantages of BiRs include high local force capacity, improved strength, a relatively high stiffness and the possibility of ductile behaviour. They also off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Depending on their actual mechanical features and capacities, as well as sensitivity to external conditions, the structural performance assessment of the building as a whole can be strongly affected. In this regard, a first set of research papers is dedicated to the experimental, numerical or hybrid analysis of special joints for constructional systems, under a variety of mechanical properties and loading conditions [2][3][4][5][6]. For timber structures, for example, it is known that both material and geometrical parameters for connections arrangement can have severe effects on mechanical performances, in the same way of moisture, loading protocol, etc.…”
Section: Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on their actual mechanical features and capacities, as well as sensitivity to external conditions, the structural performance assessment of the building as a whole can be strongly affected. In this regard, a first set of research papers is dedicated to the experimental, numerical or hybrid analysis of special joints for constructional systems, under a variety of mechanical properties and loading conditions [2][3][4][5][6]. For timber structures, for example, it is known that both material and geometrical parameters for connections arrangement can have severe effects on mechanical performances, in the same way of moisture, loading protocol, etc.…”
Section: Contentsmentioning
confidence: 99%
“…For timber structures, for example, it is known that both material and geometrical parameters for connections arrangement can have severe effects on mechanical performances, in the same way of moisture, loading protocol, etc. Experimental studies are thus reported in [2] for Bonded-in-Rod (BIR) connections under various operational conditions for bonding adhesives, while the study in [3] presents a critical analysis of performance indicators for timber-to-timber screwed connections with various configurations. As far as connections parameters are taken into account for steel structures are considered, several calculation approaches can be notoriously taken into account in support of design [4].…”
Section: Contentsmentioning
confidence: 99%
“…Standardized testing methods and requirements for glued-in rods are defined in the European standard EN 17334:2021 [5]. Some experimental studies on the gluing procedures of glued-in rod joints have shown important outcomes concerning the mechanical effects of elevated moisture contents [6] and temperatures [7]. 1 Viktor Norbäck, RISE Research Institutes of Sweden, Sweden, viktor.norback@ri.se 2 Pierre Landel, RISE Research Institutes of Sweden, pierre.landel@ri.se 3 Erik Dölerud, Modvion AB, Sweden, erik@modvion.com 4 Anders Wickström, RISE Research Institutes of Sweden, Sweden, anders.wickstrom@ri.se Connections with glued-in plates provide a strong and stiff joint compared to more traditional mechanical connections for timber structures, e.g., screws and dowels.…”
Section: Introduction 567mentioning
confidence: 99%
“…In fast-growing industrial sectors for infrastructure engineering, such as transportation and energy, drives for efficiency and functionality inevitably rely on a deep understanding of confined materials and adhesive joints [1,2]i.e, joining or sealing two similar or dissimilar materials is paramount to progress. Examples are found in glass fibre composite (GFRP) parts of a wind turbine rotor blades [3], trending glass bridges connected to metallic or wooden frames [4], and timber construction with in-rod mounting [5]. In many of these instances, the assumption of idealised and seamless joints are commonly far from ideal to be considered in calculations, and disregarding their intrinsic characteristic dimensions and constitutive behaviour is more often than not leading fundamental design flaws.…”
Section: Introductionmentioning
confidence: 99%